Supporting students in practice part 2: role of the training practice team. (2nd November 2022) - Holt, Susan L; Vivian, Sarah; Hooper, Susan
Abstract : The clinical learning environment is a complex sociocultural landscape that can be challenging to manage to support the appropriate professional development of student veterinary nurses (SVNs). The clinical supervisor is appointed to support student training in veterinary practice and is the student's first point of contact in the clinical setting. Research has shown that the wider practice team can also have a significant impact on the student experience, creating a positive or negative atmosphere for learning. It is vital that the whole team contributes to student support to create opportunities for growth and development. Being approachable and friendly, and inviting discussions, are some of the ways this can be accomplished. The presence of students in practice will also bring multiple benefits to the practice team, including a renewed perspective to problem solving and the latest evidence-based practice.